Perceived Gender wise Judgement of NETs on English Language Errors - Maharjan, Laxmi Bahadur (Mangal Research Journal, 2023)
The purpose of this study entitled 'Perceived Gender wise Judgement of English Language Errors' was to evaluate and determine the gravity of English language errors in terms of acceptability and intelligibility by the native English speaking teachers. Quantitative research methodology was utilized in this study. An error evaluation questionnaire consisting of 100 questions which were collected from the works of the higher secondary school level students was prepared with a Likert scale survey. The questionnaire was mailed to the teachers of colleges and universities of the native English speaking countries and 100 useable surveys were received electronically for a response rate of 50%, which is a good response rate for a mail survey. Received responses were analyzed using an SPSS programme and explained descriptively. The result of the study revealed that country wise native English speaking teachers judge the ESL errors alike in acceptability judgement whereas in intelligibility judgement, female teachers are found to judge the errors slightly ahead by 3.49%. Overall, both these sub-groups of teachers have perceived the errors almost similar. Moreover, the results reveal that out of the five country English speaking teachers, Australian male teachers have shown their most severity in evaluation of errors and the New Zealander teachers employed lenient patterns in their evaluation patterns. Likewise, the most severe male teachers are the Australian teachers (77.55%/58.78%) and the most severe female teachers are the New Zealander (70.96%) and American (70.12%/56.13%) teachers whereas the most lenient male teachers are the Canadian teachers (56.62%/44.10%) and the most lenient female teachers are the Australian (65.98%) and Canadian (50.84%) teachers. It is recommended that the native English speaking teachers’ evaluation of the learner errors should direct to formulate a common error evaluation pattern which can be utilized in the classrooms so that the teachers of English become aware of such universal rating scales of the ESL errors.